Digital copy reference denture: enhancing accuracy and comfort in edentulous geriatric patients: Case report - Aditia Kencana Tanuwijaya; Gian Nur Alamsyah (Indonesia Prosthodontic Association, 2026)
Introduction: Prosthodontic rehabilitation in geriatric patients is often complicated by systemic frailty, reduced neuromuscular adaptability, and limited tolerance for prolonged dental procedures. Conventional denture fabrication frequently requires multiple clinical visits and extended chairside time, which may increase treatment burden and compromise patient comfort. Advances in digital dentistry have enabled streamlined workflows that improve efficiency and predictability. The digital copy reference denture technique allows replication of an existing prosthesis while enabling controlled modification of functional and esthetic parameters, thereby facilitating patient adaptation and reducing clinical complexity. Case Presentation: A 93-year-old woman presented with poor denture retention and instability, leading to impaired mastication. Clinical examination revealed a maxillary complete denture with a suction cup causing palatal mucosal trauma and a mandibular partial denture retained by wire clasps on extruded teeth 33 and 43. Treatment involved fabrication of a new maxillary complete denture using a digital copy denture workflow while re-establishing vertical dimension and centric relation with a leaf gauge. A mandibular overdenture with magnetic attachments was planned. The digital workflow comprising intraoral scanning, digital design, and 3D printing enabled delivery of the definitive prostheses at the second visit while preserving familiar denture contours to facilitate adaptation. Conclusion: A fully digital copy reference denture workflow represents a predictable and patient-centered treatment strategy for prosthodontic rehabilitation in elderly patients. By reducing clinical visits and improving prosthesis retention, stability, and comfort, this approach offers an effective alternative for managing complex geriatric cases.